Current Updates on Pathogenesis, Systemic Therapy, and Treatment of Invasive Fungal Infections - Singh, Sushil Kumar; Pancholi, Shyam Sunder (Current Drug Targets, 2025)
Numerous health hazards are associated with fungal infections, ranging from asymptomatic cases to potentially fatal invasive diseases that are especially dangerous for those with impaired immune systems. The main causes behind these diseases are opportunistic fungi, namely Aspergillus, Candida, and Cryptococcus. Invasive fungal infections (IFIs) require a global response that includes the development of vaccines, standardized protocols for diagnosis, potent antifungal medications, and strategies to stop drug-resistant strains. Improving high-risk group diagnosis and treatment is essential to lowering death rates. This review highlights the substantial health concerns associated with fungal infections, especially in immunocompromised individuals, and identifies Aspergillus, Candida, and Cryptococcus as the main pathogens. It highlights the necessity of international efforts, such as the development of novel diagnostic instruments, imaging methods, and antifungal drugs, to combat these invasive infections. The review also addresses the increasing need for novel treatment approaches in light of the developing resistance to widely used antifungal medications. Furthermore, the significance of secretory proteins in fungal pathogenicity and the potential of combination therapy are investigated. It is also suggested that a multimodal strategy be used to fight these illnesses, given the promise of multivalent vaccinations. Overall, this study emphasizes how critical it is to develop better diagnostic and treatment strategies in order to successfully control and lessen the impact of invasive fungal diseases on the health of the world.
Keywords: combination therapies